PTH-002 Survival after upper gi stent insertion: a retrospective audit from a single centre. (17th June 2017) - Smart, H; Cooper, C; Carr, C; Haslam, N; O'Toole, P; Moore, A; Ramesh, J; Sarkar, S
Abstract : Introduction: The insertion of self-expanding metal mesh stents (SEMS) is often employed in the palliation of upper GI malignancy or in patients with benign disease who are unfit for more aggressive intervention. Technical and clinical outcomes are usually predictable and good. It is more difficult to predict patient survival; this audit was undertaken to address this outcome. Method: Patients undergoing upper GI SEMS insertion between 1 st January and 31 st December 2016 were identified from an endoscopy software system (Unisoft). Patients' demographic data and outcome was obtained by interrogation of the hospital computerised laboratory records system (ICE), Somerset Cancer Registry (SCR) and pathological records. Results: 76 upper GI SEMS were inserted in 59 patients between 1 st January and 31 st December 2016. There were 42 men and 17 women. The mean age of the group was 68.5 (range 41–89) years. SEMS insertion – This was undertaken by experienced endoscopists utilising fluoroscopy in all cases. Oesophageal SEMS used were all fully covered, either Wallflex Oesophageal (Boston Scientific) or Niti-S Double (Taewoong) and inserted using the over-the-wire technique. Gastric outflow SEMS were either Evolution Duodenal uncovered (Cook Medical) or Niti-S S pyloric/duodenal fully covered (Taewoong). These were inserted using the through-the-scope method. Oesophageal SEMS insertion – This was undertaken in 49 patients; 46 had oesophageal or oesophago-gastric junctional cancer, 2 extrinsic compression from lung cancer and 1 benign post-operative anastomotic stricture. 1 or more repeat interventions were required in a total of 17 (35%) patients. This included 17 repeat SEMS insertions, 5 reposition of SEMS, 1 removal for pain and 1 argon plasma coagulation recanalisation of hyperplastic overgrowth. 37 patients (75%) died after a median follow up of 99 (range 3–485) days. The median survival was 89 (range 3–485) days. Gastric outflow SEMS insertion – This was performed in 10 patients; 5 had pancreatic cancer, 2 post-operative recurrence of oesophago-gastric cancer, 1 gastric cancer, 1 post-operative anastomotic stricture (Whipple's procedure) and 1 chronic pancreatitis. 2 patients (20%) had repeat intervention; 1 removal (benign disease) and 1 stent dilatation. 7 patients (70%) died after a median follow up of 80 (range 8–232) days. The median survival was 56 (range 8–110) days. Conclusion: We know that upper GI SEMS insertion produces palliation of distressing symptoms in patients with advanced disease. In this audit we have defined that between 20%–35% of patients require an endoscopic re-intervention to their SEMS. Survival in both patient groups is limited, with a median survival of between 2 and 3 months. This data should inform discussion in patients regarding end of life planning. Disclosure of Interest: None Declared